All-solid-state battery

By using Si-based active substances with a specific void volume ratio in the negative electrode layer of the all-solid battery, the problem of increasing resistance after the charge and discharge cycle is solved, and the stability of battery performance and the extension of life is achieved.

CN114512636BActive Publication Date: 2025-02-07TOYOTA JIDOSHA KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111104981.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-17
Filing Date
2021-09-22
Publication Date
2025-02-07
Estimated Expiration
2041-09-22

AI Technical Summary

Technical Problem

The resistance of existing all-solid batteries increases after charging and discharging cycles, resulting in performance deterioration.

Method used

By using Si-based active substances with a specific void volume ratio in the negative electrode layer, specifically, the ratio of the sum of void volumes (VV1) in the secondary particles and the sum of void volumes between the primary particles (VV2) (VV1/VV2) is set to 0.8 or more and 5 or less to suppress the increase in resistance after cycle.

Benefits of technology

It effectively reduces the resistance value after cycling, extends the battery life, and improves the battery's cycle characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114512636B_ABST
    Figure CN114512636B_ABST
Patent Text Reader

Abstract

Provided is an all-solid-state battery capable of suppressing resistance after cycling to a low level. The all-solid-state battery comprises a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, wherein the negative electrode layer contains a Si-based active material, the Si-based active material is a secondary particle having a plurality of primary particles, and the sum of the void volumes in the primary particles contained in the secondary particles is set to V V1 , and the sum of the void volumes between the primary particles contained in the secondary particles is set as V V2 When V V1 / V V2 Calculated V V1 Relative to V V2 The ratio is 0.8 or more and 5 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to all-solid-state batteries. Background Art

[0002] All-solid-state batteries are batteries having a solid electrolyte layer between a positive electrode and a negative electrode, and have the advantage of being easy to simplify safety devices compared to liquid-based batteries having an electrolyte solution containing a flammable organic solvent.

[0003] Patent Document 1 discloses that a Si-based active material can be made porous to reduce the volume expansion rate, thereby improving the battery life.

[0004] Patent Document 2 discloses a secondary particle having a plurality of primary particles with respect to a Si-based active material, wherein the volume of the secondary particle is V P , and the void volume of the secondary particles is set to V V In the case of V V Relative to V P The ratio (V V / V P ) is greater than or equal to 0.3 and less than or equal to 0.6.

[0005] Prior art literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2018-120866

[0007] Patent Document 2: Japanese Patent Application Publication No. 2020-087882 Summary of the invention

[0008] The volume change of Si-based active materials during charge and discharge is large, so cracks are generated due to repeated charge and discharge cycles, and the resistance is easily increased. In the prior art, there is a problem of high resistance after cycling. The present disclosure is completed in view of the above actual situation, and its main purpose is to provide a fully solid-state battery that can suppress the resistance after cycling to a low level.

[0009] As one of the means to solve the above-mentioned problems, the present application discloses an all-solid-state battery, which has a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, wherein the negative electrode layer contains a Si-based active material, and the Si-based active material is a secondary particle having a plurality of primary particles, and the sum of the void volumes in the primary particles contained in the secondary particles is set as V V1 , and the sum of the void volumes between the primary particles contained in the secondary particles is set as V V2 When V V1 / V V2 Calculated V V1 Relative to V V2 The ratio is 0.8 or more and 5 or less.

[0010] The all-solid-state battery disclosed in the present application can suppress the resistance after cycling to a low level. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 It is a schematic cross-sectional view of the all-solid-state battery 10 .

[0012] Figure 2 It is a diagram schematically showing one secondary particle 20 .

[0013] Figure 3 It is a graph showing the results of Examples and Comparative Examples.

[0014] Description of Reference Numerals

[0015] 10... all-solid-state battery, 11... positive electrode layer, 12... negative electrode layer, 13... solid electrolyte layer, 14... positive electrode current collector, 15... negative electrode current collector DETAILED DESCRIPTION

[0016] Hereinafter, the all-solid-state battery of the present disclosure will be described in detail.

[0017] Figure 1 : is a schematic cross-sectional view showing an example of an all-solid-state battery in the present disclosure. Figure 2 It is a schematic cross-sectional view of one Si-based active material 20 (secondary particle 20 ) in the present disclosure. Figure 1 The all-solid battery 10 shown has a positive electrode layer 11, a negative electrode layer 12, and a solid electrolyte layer 13 disposed between the positive electrode layer 11 and the negative electrode layer 12. In addition, the all-solid battery 10 has a positive electrode collector 14 for collecting current from the positive electrode layer 11 and a negative electrode collector 15 for collecting current from the negative electrode layer 12. Each structure is described below.

[0018] 1. Negative electrode layer

[0019] The negative electrode layer 11 is a layer containing at least a negative electrode active material.

[0020] The negative electrode layer 11 contains a Si-based active material 20 as a negative electrode active material. The Si-based active material 20 is preferably an active material that can be alloyed with Li. Examples of the Si-based active material 20 include Si simple substance, Si alloy, and Si oxide. The Si alloy preferably contains Si element as a main component. The proportion of Si element in the Si alloy can be, for example, 50 mol% or more, 70 mol% or more, or 90 mol% or more.

[0021] As Si oxide, SiO2 can be mentioned, for example.

[0022] like Figure 2 As shown, the Si-based active material 20 is a secondary particle 20 having a plurality of primary particles 21 .

[0023] Here, in the Si-based active material 20, the sum of the void volumes in the primary particles 21 included in the secondary particles 20 is defined as V. V1 , and the sum of the void volumes between the primary particles 10 contained in the secondary particles 20 is defined as V V2 When V V1 / V V2 Calculated V V1 Relative to V V2 The ratio is 0.8 or more and 5 or less. Thus, the expansion and contraction suppression effect of the Si-based active material 20 can be maintained (or improved) and the initial resistance can be reduced. This is believed to be due to the expansion of the contact interface area between the Si particles and the solid electrolyte and the reduction of the solid diffusion distance in the Si. Thus, the resistance value after the cycle can be reduced. V V1 / V V2 It is preferably 1 or more, and more preferably 1.5 or more. V1 / V V2 It is preferably 5 or less, and more preferably 3 or less.

[0024] Think V V1 / V V2 When the primary particle 21 is enlarged, pores appear on the surface of the primary particle 21, the specific surface area increases, and the resistance decreases due to the increase in the reaction area. Furthermore, it is believed that the true specific gravity of the primary particle 21 decreases, so if the design has the same capacity, the number of particles increases, the reaction area increases, and the resistance decreases. In addition, it is believed that the expansion of the primary particle 21 itself can be absorbed to a certain extent by the gaps in the primary particle 21, even if V V2 The ratio of V can also be reduced, and the expansion of the secondary particles 20 can be controlled. V1 / V V2 If the value exceeds 5, the true specific gravity of the primary particles 21 becomes smaller. Therefore, if the design has the same capacity, the number of particles increases, the film thickness becomes too thick, the resistance in the thickness direction becomes larger, the area for the secondary particles 20 to absorb and expand becomes smaller, the cycle is easy to deteriorate, and the resistance after the cycle becomes larger. On the other hand, if V V1 / V V2 When the ratio is less than 0.8, the reaction area becomes relatively small, the initial resistance becomes large, and thus the resistance after the cycle becomes large.

[0025] V V1 、V V2 For example, it can be obtained as follows.

[0026] That is, the secondary particles 20 generally include V V1 、V V2 And other V α These three types of voids can be separated by the following method to obtain their respective volumes.

[0027] (1) The total void volume contained in the secondary particle 20 is obtained by gas adsorption. This is V V1+ V V2 +V α .

[0028] (2) The secondary particles 20 are crushed to the level of primary particles, and the void volume is calculated by gas adsorption. This indicates V V1 , so set it to V V1 .

[0029] (3) Therefore, through (1) and (2), we can also get V V2 +V α .

[0030] (4) The cross section of the secondary particle 20 is subjected to SEM image processing to calculate the V V2 The area and belongs to V α The area of ​​V V2 and V α The volume ratio of V V2 .

[0031] In addition, in the present disclosure, when the length of the long side of the primary particle 21 is set to a, the length of the short side is set to b, and the ratio of b to a is set to b / a, the value of b / a is, for example, greater than 0.5, greater than 0.6, or greater than 0.8. On the other hand, the value of b / a can be 1 or less than 1. When such a primary particle 21 is used, an all-solid battery with better cycle characteristics can be obtained.

[0032] The long side length a and the short side length b can be obtained by measuring the cross-sectional image of the primary particle 21. Specifically, one primary particle 21 is determined based on the cross-sectional image, and a straight line is drawn in a specific area, and the maximum length portion is set as the long side a. On the other hand, the length portion that is orthogonal to the long side a and has the smallest length is set as the short side b. Based on these values, b / a is obtained. This operation is also performed on other primary particles 21 to obtain the average value of b / a. The number of samples is preferably large, for example, more than 20, more than 50, or more than 100.

[0033] The average particle size (D 50 ) is not particularly limited, and may be, for example, 50 nm or more, or 100 nm or more. On the other hand, the average particle size (D 50 ) can be, for example, less than 1 μm or less than 500 nm.

[0034] The Si-based active material 20 in this embodiment may contain a needle-shaped conductive material between a plurality of primary particles 21. Here, the needle-shaped refers to an elongated shape in which the length of the long side is more than twice the length of the short side. In addition, the so-called needle-shaped may be a straight line shape or a curved shape, and may be referred to as a rod-shaped or fibrous shape. In addition, a plurality of needle-shaped conductive materials may exist in a entangled manner. It is presumed that such a conductive material plays the role of a filler by existing between a plurality of primary particles 21, and can have a favorable effect on the skeleton maintenance of the Si-based active material 20 during expansion and contraction of the Si-based active material 20.

[0035] The conductive material is not particularly limited as long as it is needle-shaped, and examples thereof include VGCF (vapor grown carbon fiber) and CNT (carbon nanotube).

[0036] In the needle-shaped conductive material, the long side length is at least twice the short side length, for example, may be at least 10 times, or may be at least 50 times. On the other hand, the long side length may be at most 500 times, or may be at most 100 times the short side length.

[0037] The long side of the needle-shaped conductive material is, for example, 5 μm or more and 15 μm or less. Also, the short side of the needle-shaped conductive material is, for example, 50 nm or more and 200 nm or less.

[0038] The Si-based active material 20 may contain a conductive material other than a needle-shaped material such as a granular material. Examples of the granular conductive material include acetylene black (AB) and Ketjen black (KB).

[0039] The proportion of the needle-shaped conductive material contained in the Si-based active material 20 is not particularly limited, and may be, for example, 0.5% by weight or more, or 1% by weight or more. In addition, the proportion of the conductive material may be, for example, 10% by weight or less, or 5% by weight or less. If the proportion of the conductive material is too small, the effect of including the conductive material may not be fully enjoyed. On the other hand, if the proportion of the conductive material is too large, productivity may deteriorate.

[0040] The Si-based active material 20 may have a binder between adjacent primary particles 21. As the binder, for example, polyimide can be cited. In addition, a general binder used in the negative electrode layer can also be used. The proportion of the binder contained in the Si-based active material 20 is, for example, 0.5% by weight or more, and can also be 1% by weight or more. On the other hand, the proportion of the binder contained in the Si-based active material is, for example, 5% by weight or less.

[0041] The Si-based active material 20 can be produced, for example, as follows.

[0042] For the primary particles 21, for example, Li and Si can be mixed in a mortar to prepare a LiSi alloy, and the LiSi alloy can be treated with ethanol to obtain a porous (V V1 primary particles 21 of the voids).

[0043] Then, prepare a slurry containing the obtained primary particles 21, a conductive material (also referred to as a first conductive material), a binder, and a dispersion medium. Here, as a binder, for example, a high-strength binder such as polyimide (for example, 1% by weight or more and 5% by weight or less relative to Si) can be cited, and as a dispersion medium, for example, water can be cited. In addition, as a method for forming the slurry, a method for mixing a mixture containing the primary particles 21, the first conductive material, a binder, and a dispersion medium using a mixing device such as a planetary mixer can be cited. The solid content concentration of the slurry is, for example, 5% by weight or more and 30% by weight or less.

[0044] Next, the obtained slurry is subjected to granulation treatment to form secondary particles. As a granulation treatment, for example, a treatment using a nozzle-type spray dryer can be cited. The liquid delivery rate is, for example, greater than 20 mL / h and less than 200 mL / h. The spray gas pressure is, for example, greater than 0.1 MPa and less than 0.4 MPa. In addition, the drying temperature is, for example, greater than 140°C and less than 200°C. In addition, for example, in the case where the slurry contains a polyimide precursor as a binder, it is preferably heat-treated after the granulation step to form a polyimide. The heat treatment temperature is, for example, greater than 250°C and less than 350°C. The heat treatment time is, for example, greater than 1 hour and less than 10 hours. The heat treatment atmosphere is preferably an inert atmosphere or a vacuum. Because this can prevent oxidation of the Si-based active material.

[0045] The voids (comprising V V2 The voids) can be adjusted by appropriately setting the manufacturing conditions. For example, when the solid content of the slurry is reduced, the voids tend to become larger. On the other hand, for example, if the amount of binder is increased, the voids tend to become smaller.

[0046] The negative electrode layer 11 may contain only the Si-based active material 20 as the negative electrode active material, or may further contain other active materials. In the latter case, the proportion of the Si-based active material in all the negative electrode active materials may be 50 wt % or more, 70 wt % or more, or 90 wt % or more.

[0047] The proportion of the negative electrode active material in the negative electrode layer 11 is, for example, 20% by weight or more, 30% by weight or more, or 40% by weight or more. On the other hand, the proportion of the negative electrode active material in the negative electrode layer is 95% by weight or less, 90% by weight or less, or 80% by weight or less.

[0048] In addition, the negative electrode layer 11 may contain at least one of a solid electrolyte and a binder as needed. As the above-mentioned solid electrolyte, for example, inorganic solid electrolytes such as sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and halide solid electrolytes can be cited. As a sulfide solid electrolyte, for example, a solid electrolyte containing Li element, X element (X is at least one of P, Si, Ge, Sn, B, Al, Ga, In) and S element can be cited. In addition, the sulfide solid electrolyte may also contain at least one of O element and halogen element. In addition, as an oxide solid electrolyte, for example, a solid electrolyte containing Li element, Y element (Y is at least one of Nb, B, Al, Si, P, Ti, Zr, Mo, W, S) and O element can be cited. In addition, as a nitride solid electrolyte, for example, Li3N can be cited, and as a halide solid electrolyte, for example, LiCl, LiI, LiBr can be cited. Examples of the binder include rubber-based binders such as butadiene rubber (BR) and styrene butadiene rubber (SBR), and fluoride-based binders such as polyvinylidene fluoride (PVDF).

[0049] In addition, the negative electrode layer 11 may contain a second conductive material in addition to the conductive material (first conductive material) contained in the Si-based active material 20. As the second conductive material, for example, a carbon material can be cited. As the carbon material, for example, granular carbon materials such as acetylene black and Ketjen black, and fibrous carbon materials such as carbon fibers, carbon nanotubes, and carbon nanofibers can be cited. The second conductive material may be different from the first conductive material or may be the same, but preferably the same.

[0050] When the negative electrode layer 11 contains the first conductive material and the second conductive material, the ratio of the first conductive material in all conductive materials in the negative electrode layer may be 50 wt % or more, 70 wt % or more, or 90 wt % or more.

[0051] The thickness of the negative electrode layer 11 is, for example, 0.1 μm or more and 1000 μm or less. As a method for forming the negative electrode layer, for example, a method of applying a slurry containing at least the above-mentioned secondary particle-formed Si-based active material and a dispersion medium and drying the slurry can be cited. Furthermore, the second conductive material can be added when preparing the above-mentioned slurry.

[0052] 2. Positive electrode layer

[0053] The positive electrode layer 12 is a layer containing at least a positive electrode active material. In addition, the positive electrode layer 12 may contain at least one of a solid electrolyte, a conductive material, and a binder as necessary.

[0054] Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO2, LiMnO2, LiNiO2, LiVO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and other rock salt layered active materials, LiMn2O4, Li(Ni 0.5 Mn 1.5 )O4 and other spinel active materials, LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4 and other olivine active materials. In addition, a coating layer containing a Li ion conductive oxide can be formed on the surface of the positive electrode active material. This is because it can inhibit the reaction between the positive electrode active material and the solid electrolyte.

[0055] The shape of the positive electrode active material may be, for example, a granular shape. The average particle size (D 50 ) is not particularly limited, and may be, for example, 10 nm or more, or 100 nm or more. On the other hand, the average particle size (D 50 ) is, for example, less than 50 μm, or less than 20 μm.

[0056] The proportion of the positive electrode active material in the positive electrode layer 12 is, for example, 20% by weight or more, 30% by weight or more, or 40% by weight or more. On the other hand, the proportion of the positive electrode active material is, for example, 80% by weight or less, 70% by weight or less, or 60% by weight or less.

[0057] The solid electrolyte and the binder used in the positive electrode layer 12 are the same as those described above for the negative electrode layer 11 , and thus description thereof is omitted here.

[0058] Examples of the conductive material include carbon materials, and examples of the carbon material include granular carbon materials such as acetylene black and Ketjen black, and fibrous carbon materials such as carbon fibers, carbon nanotubes, and carbon nanofibers.

[0059] The thickness of the positive electrode layer 12 is, for example, 0.1 μm or more and 1000 μm or less. As a method for forming the positive electrode layer, for example, there is a method of applying a slurry containing at least a positive electrode active material and a dispersion medium and drying the slurry.

[0060] 3. Solid electrolyte layer

[0061] The solid electrolyte layer 13 is a layer disposed between the positive electrode layer and the negative electrode layer. The solid electrolyte layer 13 contains at least a solid electrolyte and may further contain a binder as required. The solid electrolyte and the binder are the same as those described above for the negative electrode layer 11, so they are omitted here. Among them, the solid electrolyte layer preferably contains a sulfide solid electrolyte as the solid electrolyte.

[0062] The thickness of solid electrolyte layer 13 is, for example, 0.1 μm or more and 1000 μm or less. As a method for forming solid electrolyte layer 13, for example, there is a method of compression molding a solid electrolyte.

[0063] 4. Other components

[0064] The all-solid-state battery 10 in this embodiment has at least the above-mentioned negative electrode layer 11, the positive electrode layer 12 and the solid electrolyte layer 13. Moreover, it usually has a positive electrode collector 15 for collecting the positive electrode layer 12 and a negative electrode collector 14 for collecting the negative electrode layer 11. As the material of the positive electrode collector 15, for example, stainless steel, aluminum, nickel, iron, titanium and carbon can be mentioned. On the other hand, as the material of the negative electrode collector 14, for example, stainless steel, copper, nickel and carbon can be mentioned. Furthermore, regarding the thickness and shape of the positive electrode collector 15 and the negative electrode collector 14, it is preferably selected appropriately according to the purpose of the battery. In addition, the all-solid-state battery 10 may also have a battery case 16 that accommodates the above-mentioned negative electrode layer 11, the positive electrode layer 12 and the solid electrolyte layer 13.

[0065] 5. All-solid-state batteries

[0066] The all-solid battery in the present disclosure is preferably an all-solid lithium battery. In addition, the all-solid battery in the present disclosure may be a primary battery or a secondary battery, wherein a secondary battery is preferred. Because it can be repeatedly charged and discharged, it is useful as, for example, a vehicle-mounted battery. In addition, the all-solid battery in the present disclosure may be a single cell or a stacked battery. The stacked battery may be a monopolar stacked battery (a stacked battery of a parallel type) or a bipolar stacked battery (a stacked battery of a series type). As the shape of the all-solid battery, for example, a coin type, a laminated type, a cylindrical type, and a square type may be cited.

[0067] The above-mentioned embodiments are merely examples, and all technologies having substantially the same technical concept as that described in the scope of claims for protection of the present disclosure and having the same functions and effects are included in the technical scope of the present disclosure.

[0068] [Example]

[0069] [Fabrication of positive electrode structure]

[0070] Weigh the positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2) and sulfide solid electrolyte (Li2S-P2S5) so that the volume ratio of positive electrode active material: sulfide solid electrolyte = 75:25. In addition, 1.5 parts by weight of PVDF binder are weighed for 100 parts by weight of positive electrode active material, and 3.0 parts by weight of conductive aid (VGCF, manufactured by Showa Denko) are weighed for 100 parts by weight of positive electrode active material. These materials are mixed and adjusted to a solid fraction of 63% by weight. Then, an ultrasonic homogenizer is used to mix for 1 minute to obtain a slurry-like positive electrode composition. The obtained positive electrode composition is applied to the surface of the positive electrode collector (aluminum foil, manufactured by Showa Denko), and a positive electrode is formed through a heating and drying process. Rolling is performed at 25°C and a linear pressure of 1 ton / cm to obtain a positive electrode structure having a positive electrode collector and a positive electrode layer.

[0071] [Preparation of negative electrode active material]

[0072] Li and Si were mixed in a mortar to prepare a LiSi alloy, and the LiSi alloy was treated with ethanol to obtain porous primary particles.

[0073] The prepared primary particles, a conductive material (VGCF, manufactured by Showa Denko Co., Ltd.) having a length of 6 μm and a diameter of 150 nm, a precursor of polyimide (polyamic acid) and water were mixed and mixed with a planetary mixer to obtain a slurry. The obtained slurry was dried using a nozzle-type spray dryer to form secondary particles. Then, heat treatment was performed under an inert atmosphere to obtain a Si-based active material.

[0074] The obtained Si-based active material is used to obtain V V1 / V V2 . V in Examples 1 to 5, Comparative Examples 1 and 2 V1 / V V2 The V in each example is shown in Table 1. V1 / V V2 The adjustment of V is done by adjusting the mixing ratio of Li and Si and the ethanol treatment rate. V1 , V can be adjusted by the spray pressure and / or drying speed of the spray dryer V2 And carried out.

[0075] [Fabrication of negative electrode structure]

[0076] The prepared Si-based active material and sulfide solid electrolyte (Li2S-P2S5) are weighed so that the volume ratio of negative electrode active material: sulfide solid electrolyte = 60:40. In addition, 1.5 parts by weight of PVDF binder are weighed for 100 parts by weight of Si-based active material, and 3.0 parts by weight of conductive aid (VGCF) are weighed for 100 parts by weight of Si-based active material. Then, these materials are mixed and adjusted so that the solid fraction is 45% by weight. Then, an ultrasonic homogenizer is used to mix for 1 minute to obtain a slurry-like negative electrode composition. The obtained negative electrode composition is applied to the surface of the negative electrode collector (nickel foil) with an applicator and heated to dry. Then, roller pressing is performed at 25°C and a linear pressure of 1 ton / cm to obtain a negative electrode structure having a negative electrode collector and a negative electrode layer. Furthermore, V shown in Table 1 V1 / V V2 This is the measurement result before pressing, but the inventors confirmed that V V1 / V V2 Almost no change.

[0077] [Battery production]

[0078] The sulfide solid electrolyte (Li2S-P2S5) and the PVDF binder are weighed so that the PVDF binder is 1 part by mass relative to 100 parts by weight of the sulfide solid electrolyte, and the solid fraction is 63% by mass. The mixture is mixed for 1 minute using an ultrasonic homogenizer to prepare a slurry-like diaphragm composition. Then, the slurry-like diaphragm composition is applied to the surface of the aluminum foil, and a diaphragm layer is formed by a heating and drying process. Next, the diaphragm layer is transferred to the positive electrode structure, and then the negative electrode structure is transferred to prepare the diaphragm layer and the battery cell.

[0079] [evaluate]

[0080] For the batteries obtained in Examples 1 to 5, Comparative Example 1, and Comparative Example 2, charge and discharge were performed for 500 cycles at 3.0V to 4.2V, and the resistance value at the 500th cycle was taken as the resistance value after the cycle. Here, the resistance value is calculated based on the voltage difference (ΔV) when discharging at 4C (C rate) for 1 second from SOC (State Of Charge) 20%. Then, the resistance value after the cycle of Example 3 is set to 1.0, and the ratio of the resistance value after the cycle of each example (resistance ratio after the cycle) is calculated. The results are shown in Table 1. In addition, the horizontal axis is V V1 / V V2 , and the vertical axis is the coordinate diagram of the resistance ratio after cycling. Figure 3 .

[0081] Table 1

[0082] <![CDATA[V V1 / V V2 ]]> Resistivity after cycling Example 1 5.0 1.05 Example 2 3.0 1.01 Example 3 1.5 1.00 Example 4 1.0 1.01 Example 5 0.8 1.02 Comparative Example 1 7.0 1.09 Comparative Example 2 0.5 1.08

[0083] From Table 1, Figure 3 It can be seen that by setting V V1 / V V2 By setting the ratio to 0.8 to 5.0, the resistance ratio after cycles can be suppressed to be low.

Claims

1. An all-solid-state battery comprising a positive electrode layer, a negative electrode layer, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer, The negative electrode layer contains Si-based active material, The Si-based active material is a secondary particle having a plurality of primary particles. The sum of the void volumes in the primary particles contained in the secondary particles is defined as V V1 , and the sum of the void volumes between the primary particles contained in the secondary particles is set to V V2 When V V1 / V V2 The calculated V V1 With respect to the V V2 The ratio is 0.8 or more and 3 or less.

Citation Information

Patent Citations

  • Porous silicon-based anode active material, method for preparing the same, and lithium secondary battery comprising the same

    JP2018120866A

  • All-solid battery

    JP2020087882A

  • Method of producing electrochemically stable anode particulates for lithium secondary batteries

    US20200119340A1